Malayalam Dalit Short Story: Coming Of Age - Muhammed Saleem.P.M (International Journal of English Language, Literature and Humanities, 2015)
This paper attempts to trace the origin and growth of Malayalam Dalit short story. The paper argues that the short story in Malayalam has undergone three specific periods in relation to its thematic and ideological considerations. The first phase is represented by T.K.C. Vaduthala who attempted to portray the real life experience of Dalits in Kerala in his works. For the first time, Dalit voice is clearly seen in the field of short story. He attempted to consider the options of conversion to different religions and embracing of communist ideology to liberate the Dalit community from the clutches of caste discrimination. The second phase is marked by an antagonism towards religious conversion and represented by writers such as Paul Chirakkode . It is in the third phase that the Dalits realize the importance to assert their identity and cultural past to fight against the different forms of oppression that they face today. In the field of short story this change is reflected in the short stories of C. Ayyappan. The article elaborates the idea with specific examples and offers a platform for conducting further researches in the field of Malayalm Dalit short story